Complexity of Work‐Life Identities and Policy Development: Implications for Work‐Life in Higher Education. Issue 176 (December 2016) - Lester, Jaime
Abstract : This chapter describes the themes that emerged in this volume with attention to important policy implications on the federal, state, and institutional levels. Recommendations for future research are provided.